Increased Inceptisol Soil Fertility as well as Growth and Production of Soybeans due to Compost Enriched Eggshells and Beneficial Microbes - Hady Nour Falaqh; T Sabrina; Fauzi Fauzi (Jurnal Agroekoteknologi, 2018)
The availability of nutrients in the soil is a major factor affected the growth and production of plants. This study aims to determine the response of compost enriched chicken egg shell and beneficial microbes (rhyzobium + mycorrhiza) to some aspects of soil properties of Inseptisol as well as the growth and production of soybeans. This research was conducted in field trial UPT Balai Induk Palawija Tanjung Selamat and Soil Biology Laboratory Faculty of Agriculture University of North Sumatra. This research used was a Factorial Random Block Design. The first factor was chicken egg shell enriched consist of 4 treatments 0 ton/ha, 10 ton/ha, 20 ton/ha, 30 ton/ha and second factor was beneficial microbe (rhyzobium + mycorrhiza) consist of 2 treatmenst 0 g/polybag and 10 g/polybag. The results showed that the enriched compost enriched chicken egg shell increased the soil pH, C-organic, Ca-exchanged, shoot dry weight , the amoont of root nodule, percentage of degree of root infected by mycorrhiza, and weight of 100 seeds and the application of beneficial microbes increased root nodule and root infection degree.